2010
DOI: 10.1002/mrd.21186
|View full text |Cite
|
Sign up to set email alerts
|

The equine oocyte: Factors affecting meiotic and developmental competence

Abstract: SUMMARYThere is currently much interest in assisted reproduction techniques in the horse, however, many aspects of oocyte maturation, fertilization, and embryo development in the horse differ from those in other species. Because of the close attachment of the equine oocyte to the follicle wall, scraping of the follicle is the most effective method for oocyte recovery. A notable feature of equine oocytes is that those with expanded cumuli (Ex oocytes), which originate from atretic follicles, have higher meiotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 92 publications
(136 reference statements)
4
44
1
Order By: Relevance
“…The early observation that the process of follicle selection would create subordinate follicles containing more competent oocyte was made in the bovine model [32,35], but over the last decade, similar observations were made especially in mono-ovulating species like the horse [36]. The first question that arises from such observation is why would oocytes from dying follicles be better?…”
Section: The Mystery Of Early Atresiamentioning
confidence: 92%
“…The early observation that the process of follicle selection would create subordinate follicles containing more competent oocyte was made in the bovine model [32,35], but over the last decade, similar observations were made especially in mono-ovulating species like the horse [36]. The first question that arises from such observation is why would oocytes from dying follicles be better?…”
Section: The Mystery Of Early Atresiamentioning
confidence: 92%
“…ICSI has become the method of choice for the fertilization of equine oocytes in the laboratory because of the failure of standard IVF in this species (see Hinrichs (2010)). However, success in equine in vitro embryo production is variable, and few laboratories have reported repeatable blastocyst rates of more than 15% per injected oocyte.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the analysis of H4K8, H4K12 and H4K16 acetylation pattern revealed that the progressive chromatin rearrangement from fibrillar to condensed configuration is characterized by a decrease of acetylation at K8 and K12 residues and by an increase of acetylation at K16 residue. These data are of particular interest since the process of chromatin remodeling that precedes the resumption of meiosis has been recognized as a marker of oocyte final differentiation and associated with the acquisition of meiotic and developmental competences (De La Fuente, 2006) in several species, including the horse (Hinrichs and Williams, 1997;Hinrichs and Schmidt, 2000;Dell'Aquila et al, 2001;Hinrichs et al, 2005;Hinrichs, 2010). Histone acetylation has been recognized as one of the mechanisms implicated in GV large-scale chromatin remodeling (De La Fuente et al, 2004;Kageyama et al, 2007) and provides an important epigenetic mechanism for the developmental control of global gene expression (De La Fuente, 2006).…”
Section: Discussionmentioning
confidence: 99%